Catch patterns of the German Baltic Sea trawl fleet targeting demersal species between 2006 and 2009 - W.N. Probst; U. Berth; D. Stepputtis; C. Hammer (Acta Ichthyologica et Piscatoria, 2011)
Background. The data collection of commercial fisheries has been formalized by the EU data collection framework (DCF). Besides gaining relevant information to fisheries management under the Common Fisheries Policy, the data of the DCF will gain importance in assessing the impacts of fishing on the ecosystem of the Baltic Sea. Materials and methods. The catch of the demersal German Baltic Sea trawl fleet between 2006 and 2009 was sampled by on-board observers to investigate the temporal and spatial patterns in catch composition. Results. There was a general increment in tow duration, landing weights, and discard weights from west to east. The most important species by catch weight was cod, for which highest catches were obtained during spring in ICES subdivision 25. Single hauls exceeded 25 h and caught more than 9900 kg of cod. On average, about 5%, 13%, and 20% and of the captured cod, flounder, and dab, respectively, were discarded. Conclusion. The presently reported study provides a benchmark for the German Baltic Fisheries that can be used for assessment of new management regulations and/or new marine policies. A comprehensive documentation of the spatial and temporal catch distribution of the German Baltic demersal trawl fleet, prior to the implementation of marine spatial planning measures such as marine protected areas or offshore wind farms, should help to evaluate the implications of intensifying spatial use on the fishing industry.